A Statistical Approach for the Learning Curve of Physicians in Utilization of Electronic Order Sets - Lee, Jaehoon; Hulse, Nathan C. (Methods of Information in Medicine, 2019)
Background Understanding a physician's behavior toward learning order sets is important as it is a key information to design order sets with optimized contents.Objective The objective of this article is to test a hypothesis: for a physician using a new order set repeatedly, the utilization rate of order set contents has a pattern of either increase or decrease.Methods To test the hypothesis, we retrieved empirical data of order set usage in local hospitals that adopted a new computerized physician order entry (CPOE) system and enterprise wide standard order sets. We extracted 4-year data including 63,583 orders made by 600 physicians in the inpatient setting and analyzed patterns of the learning curve at several aggregation levels.Result The analysis results demonstrated that content modification rates over time were relatively flat except for a few localized patterns.Conclusion Based on our finding, we reject our initial hypothesis.
Keywords: order set; computerized physician order entry; learning curve; electronic health record